Performance, carcass, and meat palatability traits of open and 30-month old heifers that produced one calf - Waggoner, A.W.; Brethour, J.R.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty-seven 3/8 Simmental x 5/8 Hereford heifers calved at 2 years of age and were designated as Single-Calf-Heifers (SCH). Twenty-six heifer mates that did not calve were designated as 2-year-old open heifers (2-OH), and 22, 1 year-old open heifers (1-OH) from the same source served as controls. All heifer groups were fed a high-grain diet for 112 to 137 days before slaughter. The SCH were started on feed about 1 month after calving, and their calves were weaned early about 5 weeks prior to slaughter. Thirty-three of the SCH were implanted with Synovex-H® after calving. Carcass data were obtained, and rib steaks were collected and evaluated for palatability. Our results indicate that it is possible to produce carcasses with desirable weights, USDA quality and yield grades, and taste panel palatability ratings from heifers that have produced one calf, and then were fed a high-grain diet and slaughtered by 30 months of age. However, ribeye steaks of SCH were not as tender as those from 1-OH. Implanting heifers that have calved may result in more "hard-boned" carcasses, but likely will increase dressing percent. Cattlemen willing to provide intensive management may find that the SCH system has considerable potential.
Keywords: Beef; Performance; Carcass; Meat palatability; Open heifers; 30-month heifers